Analysis of The Main Characterâ€™s Personality in â€œThe Midnight Libraryâ€ Novel By Matt Haig - Sihotang, Devilina; Mubarak, Zia Hisni (Syntax Literate, 2024)
This research has the purpose of finding out the personality of the protagonist in the novel entitled â€œThe Midnight Libraryâ€ written by Matt Haig. The researcher had used the theory of psychoanalysis by Sigmund Freud in order to analyse on Noraâ€™s personality, the protagonist of the novel. Freud had introduced psychoanalysis on human psyche, which consisted of three aspects, they are the id, the ego, and the superego. The design of this research is descriptive qualitative research, which the data collection is using the method of library research and data analysing is using descriptive analysis method, both theorized by Ratna (2004). It results on the findings of 4 data of id aspect, 3 data of ego aspect, and 5 data of superego. It can be concluded from the analysis result that the main character of the novel, Nora Seed, was controlled the most by her superego, where she built her superego personality through her experiences and journeys in finding the right life for herself. The aspect of superego shown by Nora reflected to ideal standard of societyâ€™s moral and rules.